Devonian vertebrates from the Canning and Carnarvon Basins with an overview of Paleozoic vertebrates of Western Australia - Trinajstic, Katherine; Roelofs, Brett; Burrow, C.; Long, J.; Turner, S. (Royal Society of Western Australia, 2014)
A diverse vertebrate fauna, comprising both micro- and macrovertebrate remains, is known from the Paleozoic of Western Australia. However, it is the Late Devonian fauna of the Gogo Formation that shows exceptional preservation and which is the best known. Advances in tomographic techniques, both micro-CT and synchrotron, have revealed new histological data providing information on bone growth, muscle attachments and the evolution of teeth. The fishes from the Gogo Formation have also revealed new information on the evolution of reproductive structures and live birth in early vertebrates. Recent work on the Frasnian reefs that crop out along the Lennard Shelf and mineral drillcore through Paleozoic sedimentary rocks have yielded scales of agnathan thelodonts, and the bones, teeth and scales of sharks, acanthodians and osteichthyans, all of which have increased our knowledge of Ordovician–Late Devonian microfaunas in the Canning Basin, contributing to our understanding of biostratigraphy and correlation within Australia and globally. Less work has been undertaken in the Carnarvon Basin, although like the Canning Basin this has concentrated on Late Devonian strata. More recently, work has commenced on describing Early Carboniferous faunas from the Canning, Carnarvon and Bonaparte Basins. All this work is providing information on faunal patterns and exchange of vertebrates through the Paleozoic. However, the paleogeographic evidence provided by the vertebrates is sometimes at odds with paleogeographic reconstructions based on paleomagnetic evidence and further investigation is required to resolve these differing interpretations.